Relationship of the Eggshell Conductance Constant to Intestinal Physiology - Christensen, V.L.; Ort, D.T.; Suvarna, S.; Croom, W.J.; Jr.; Grimes, J.L. (International Journal of Poultry Science, 2003)
The hypothesis was proposed that eggshell conductance constants (k) alter embryonic intestinal development and affect growth post hatching. Egg weight (EW), eggshell conductance (G) and length of the incubation period (IP), the three components of the conductance constant were changed to determine their effect on intestinal physiology. Eggs were selected based on EW and G properties. Half of the selected eggs were incubated using a single stage temperature profile to shorten IP in each of two experiments. EW, G and IP interacted in the first experiment to affect intestinal growth and metabolism. In Experiment 2, k reduced intestinal weight in embryos as well as poults. EW and IP affected the size and maturity of intestinal tissue at the time of hatching. Differences in EW, G and IP observed at hatching were shown to affect the growth of poults for the first week following hatching. Thus, k may act to reduce growth in poults by affecting intestinal maturation. It is suggested that large eggs with low permeability may be at risk for weak poults. This may be especially true when they are exposed to shorter IP.